Potential application of papain enzyme from papaya leaves in making antibacteria and antifungal handwash and hand sanitizer - Nguang, Suok Ling (2013)
This paper presents antibacterial and antifungal study of papain enzyme and its potential in making hand wash and hand sanitizer. Papain enzyme could be obtained from papaya latex, fruits and leaves. In this research, papaya leaves chose for the papain extraction because it is biomass and easily to get the source. The extraction method used in this research is hot water extraction follow by the Folin & Ciocalteu papain analysis method. Before making the antibacterial and antifungal handwash and hand sanitizer, antibacterial and antifungal test was done in order to proof the antibacterial and antifungal properties of papain enzyme. Antibacterial and antifungal test were done by incubating the pathogens on the nutrient agar in incubator for three days then insert papain enzyme onto it then incubate for another three days to determine the mycelial growth of pathogens. A volume of 187mL of papain solution was extracted by 21.55g and 200mL water. During the papain enzyme analysis, dark blue solution formed when Folin & Ciocalteu reagent was added into the solution sample. The blue colour indicate the present of tpapain enzyme. Enzyme concentration was measured in 0.415μm while the enzyme activity is 0.2283unit/mL. It means that 10mL of the papain solution extracted contains 2.283 unit of papain enzyme. The mycelial growth of the Staphylococcus aureus, Escherichia coli and Bacillus subtilis bacteria and Saccharomyces cerevisiae, Rhizopus spp. and Mucor sppfungus were obviously decline 3 days after the papain solution added. Antibacterial and antifungal handwash and hand sanitizer were successfully produced at the end of this research